2022
DOI: 10.1021/acs.inorgchem.2c00436
|View full text |Cite
|
Sign up to set email alerts
|

Activity Measurement of Iodine Fission Products in 2LiF-BeF2Salt and Its Application in Redox Potential Surveillance for a Thorium Molten Salt Reactor

Abstract: The activities of 131I, 132I, 133I, and 135I produced by neutron-induced fission of 235U in 2LiF-BeF2 (FLiBe) eutectic salt and their dependence on the redox potential were studied. The dependence observed experimentally suggested that the activity ratio for 131I to 132I could be used as an indicator of the redox potential for FLiBe salt. Relying on the selective adsorption of iodine ions on the activated silver probe by ion exchange, a novel method for activity distribution measurement of the iodine isotopes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This is an important research topic since the iodine behavior in molten salts is not well understood. There are indications that iodine release correlates with the fluorine potential of the melt [31]. This would enable both THE monitoring of the salt's fluorine potential and provide confidence for release estimates in MSR safety analyses.…”
Section: System Monitoringmentioning
confidence: 95%
“…This is an important research topic since the iodine behavior in molten salts is not well understood. There are indications that iodine release correlates with the fluorine potential of the melt [31]. This would enable both THE monitoring of the salt's fluorine potential and provide confidence for release estimates in MSR safety analyses.…”
Section: System Monitoringmentioning
confidence: 95%
“…The behaviour of iodine ssion products and their correlation with the redox potential in the FLiBe molten salt have been studied in our previous work. 21,22 The investigations showed that as the redox potential of the molten salt increases, the iodine is oxidised into the iodine molecule I 2 and released from the salt, leading to a decrease in the iodine activity remaining in the melt. In the present work, two parallel experiments were carried out, where the specic activities of 131 I and 233 Pa in the FLiBe and their correlation with the redox potential were examined simultaneously (Fig.…”
Section: Control and Monitoring Of The Redox Potential In Nif 2oxidis...mentioning
confidence: 99%